Entre esquecimentos e resistências: vozes na primeira pessoa na literatura e no documentário - Machado Neto, Jairo de Almeida (2019)
The present study proposes to understand and trace the language procedures in first person narratives presented both in literature and documentaries. Focusing on productions related to family ties affected by the South American dictatorships and their search for resilience. The works that constitute our main corpora are the novel A resistência (2015), by the brazilian author Julián Fuks, and the script of the documentary O esquecimento (im)possível (2016), by the argentinean director Andrés Habegger. The accomplishment of this bibliographical research will include the reading and analysis of different authors, within which will be raised the theories of “self-writing” by Michel Foucault, the autobiographical pact by Philippe Lejeune and his interpretations by José Amícola, as well as writings on autofiction by Serge Doubrovsky, Philippe Gasparini, Vincent Colonna, Diana Klinger and Bruno Lima. Also, we will be exploring the documentary theories by Bill Nichols, the film-essay by Timothy Corrigan, and the first-person documentary by Pablo Piedras. The project explores such points, aiming to demonstrate how these two arts end up intersecting and influencing each other